The Figure of Dante : An Essay on The Vita Nuova - Mazzaro, Jerome (Book collections on Project MUSE., 2014)
Jerome Mazzaro examines Dante's Vita Nuova as an artistic correlative to what Dante conceived as an image of himself. Specifically, he explores the structure of the work in relation to medieval views of memory, self, music, form, and interpretation, and against the facts of Dante's life and culture as we have come to know them. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions pres.